Sperner type theorems for generalized divisors - Porubský, Štefan (Annales Mathematicae Silesianae, 2003)
The extensions of the well-known Sperner's result on antichains of subsets of a given finite set for divisors of a positive integers are shown to hold also for sets of regular systems of divisors of elements of arithmetical semigroups.